Reducing Production Defects in Indonesian Furniture Using Seven Tools and 5W+1H: Mengurangi Cacat Produksi pada Furnitur Indonesia dengan Menggunakan Tujuh Alat dan 5W+1H - Burhanudin, Asrul; Cahyana, Atikha Sidhi (Universitas Muhammadiyah Sidoarjo, 2024)
PT. Romi Violeta, an Indonesian furniture company specializing in rattan and wood products, faces frequent production defects. This study aims to identify and reduce these defects using the Seven Tools and 5W+1H methods. Qualitative data were obtained through field observations and interviews, while quantitative data were gathered using the Seven Tools approach. From February to June 2022, color variation was the most frequent defect, with the highest defect rate in March at 26.5%. Root causes included factors related to man, material, machine, method, and environment. The proposed corrective actions aim to minimize these defects, enhancing overall product quality. Future research should explore additional defect causes using different methodologies. Highlight: Defect Analysis: Identified color variation as the most frequent defect. Root Causes: Man, material, machine, method, and environment factors. Corrective Actions: Proposed solutions to minimize defects and enhance quality. Keywoard: Production defects, Seven Tools, 5W+1H, quality improvement, furniture manufacturing